Long range wireless communication by using arduino and HC- 12 Wireless Serial Module - M.Taha, Adnan; Saleh, Adham Hadi; Ahmed, Ahmed Mohammed (International Journal of Engineering and Technology, 2018)
Smart control systems are developing these days; it's become a demand for companies and, factories, and homes to control their appliances and reduce the consumption electric power. HC-12 is a Half-duplex wireless serial Communication unit has a capability of creating wireless link between two end devices. In this work, HC-12 is presented and used for controlling any electrical devices inside the company, to establish the smart control system for company appliances. HC-12 incorporate with Arduino provide a transmitter receiving system, which used for sending commands from user to the appliances via personal computer, these commands enable an controller to turn OFF or turn ON an appliance. Assembly language obtained from the Arduino IDE software to establish the integration between the microcontroller and HC-12 for proposed system. The system activated by sending the command from the end user, personal computer, to the controller, after receiving the command by microcontroller unit and carried out the proper order by switching OFF or switching ON automatically the electrical appliances inside the home or factory. The prototype system was implemented and applied tofactory and had been working successfully; besides, it provides an effective mechanism for utilization the energy eficiently.